2009
DOI: 10.1182/blood.v114.22.4054.4054
|View full text |Cite
|
Sign up to set email alerts
|

Rapid (Sixty Minutes) Infusion of One Gram of Low Molecular Iron Dextran: Safety and Efficacy Profile.

Abstract: 4054 Poster Board III-989 Introduction Many clinical situations are associated with the development of iron deficiency which can adversely affect energy level, physical activity, cardiovascular function, cognition, and immune responses. Oral iron, which is the primary treatment for iron deficiency, is limited by poor tolerability due to gastrointestinal (GI) side effects and resulting problems with compliance. In addition, in many patients it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In a study by Auerbach et al, it was found that an increased response was found in patients with follow-up evaluation 4 or more weeks following IV iron supplementation compared to those prior to 4 weeks. 11 .1%, respectively). As baseline iron labs were similar, the degree or severity of iron deficiency does not likely contribute to this difference.…”
Section: Safetymentioning
confidence: 86%
See 3 more Smart Citations
“…In a study by Auerbach et al, it was found that an increased response was found in patients with follow-up evaluation 4 or more weeks following IV iron supplementation compared to those prior to 4 weeks. 11 .1%, respectively). As baseline iron labs were similar, the degree or severity of iron deficiency does not likely contribute to this difference.…”
Section: Safetymentioning
confidence: 86%
“…Prior studies which evaluated single-dose LMWID or ferumoxytol separately reported average changes in hemoglobin of 1.2-1.9 g/dL. 7,11,12 Notably, our study utilized medians for reporting and analysis in the setting of heterogeneous data.…”
Section: Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…Despite study shortcomings and lack of definitive randomized trials, the iron sucrose Venofer and the iron gluconate Ferrlecit are believed to have lower risks of serious anaphylactic‐type reactions than the iron dextrans [20–27] possibly because they do not initiate an anti‐dextran response [25]. A stated advantage of iron dextran, besides lower cost, is the ability to infuse a patient's total iron requirement in one administration (total dose infusion) [28–30] so clinicians can conveniently treat patients in a single hospital or clinic visit. However, the total dose infusion of iron dextran, although widely used, is an off‐label method of administration [30] and it is not known if studies with adequately large sample sizes have been done to determine its relative safety.…”
Section: Discussionmentioning
confidence: 99%